2022
DOI: 10.1371/journal.pntd.0010693
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infection by pulmonary non-tuberculous mycobacteria in French Guiana 2008–2018

Abstract: Introduction Unlike diseases caused by Mycobacterium tuberculosis, M. leprae and M. ulcerans, the epidemiology of pulmonary non-tuberculous mycobacteria (PNTM) has not received due attention in French Guiana. The main objective of the current study was to define the incidence of these PNTM infections: NTM pulmonary diseases (NTM-PD) and casual PNTM isolation (responsible of latent infection or simple colonization). The secondary objectives were to determine species diversity and geographic distribution of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…L’épidémiologie des infections à mycobactéries non tuberculeuses, dites atypiques, d'expression respiratoire (MBNTER) diffère en Guyane de celle de l'Hexagone. Ainsi, une étude portant sur les infections à MBNTER entre 2008 et 2018 a identifié 178 patients dont 147 étaient porteurs asymptomatiques et 31 présentaient des symptômes compatibles avec une infection active [ 58 ].…”
Section: Pathologies Infectieuses Fébrilesunclassified
“…L’épidémiologie des infections à mycobactéries non tuberculeuses, dites atypiques, d'expression respiratoire (MBNTER) diffère en Guyane de celle de l'Hexagone. Ainsi, une étude portant sur les infections à MBNTER entre 2008 et 2018 a identifié 178 patients dont 147 étaient porteurs asymptomatiques et 31 présentaient des symptômes compatibles avec une infection active [ 58 ].…”
Section: Pathologies Infectieuses Fébrilesunclassified
“…All other mycobacteria, called nontuberculous mycobacteria (NTM), are considered conditionally pathogenic to humans and capable of causing generalized disease under certain conditions, particularly in immunocompromised individuals. Studies in North America, Europe, and Asia have shown an increased incidence of NTM in recent decades [ 2 , 3 , 4 ]. The estimated prevalence of NTM increased from 2.4 cases per 100,000 in the early 1980s to 15.2 cases per 100,000 in 2013 in the United States [ 5 ], in Canada the incidence in 2010 was as high as 20–25 cases per 100,000 population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, NTM disease increased from 9.4 in 2009 to 36.1 in 2016 cases per 100,000 population [ 7 ]. The incidence of pulmonary disease caused by NTM ranged from 1.07 in French Guiana in 2018 [ 2 ] to 4.73 in 2015 in the USA [ 8 ]. The annual prevalence in the latter study was estimated to be 11.7 per 100,000 which is caused by the long duration of the disease.…”
Section: Introductionmentioning
confidence: 99%